A REVIEW ON THE ROLE OF PPARÎ³ AGONISTS AND HYBRIDS IN TYPE 2 DIABETES AND CARDIOMYOPATHY. - Maji, Deepanwita; Samanta, Subir (Asian Journal of Pharmaceutical and Clinical Research, 2015)
Type 2 diabetes mellitus (DM) is a chronic multiple metabolic disorders characterized by increase in blood glucose level and accompanied with a number of microvascular and macrovascular complications due to lifestyle factors, genetic factors related to impaired insulin secretion and insulin resistance and environmental factors. Cardiovascular complications are one of the main causes responsible for 80% mortality rate in Type 2 diabetic patients. Recently, amino acids and peptides are emerging as very good groups of antidiabetics as well as cardioprotective drugs, which may decrease the symptoms of DM as well as take care of cardiovascular complications. Synthetic analogs of amylin and incretin mimetics are becoming ideal adjuncts to diabetes therapy. To overcome the complications related to present day oral hypoglycemic agents which includes sulfonylureas, biguanide, thiazolidinediones etc., This study has been done to review the role of peroxisome proliferator-activated receptor-Î³ agonists, amino acids and hybrid compounds for activation of adenosine monophosphate-activated protein kinase receptors, which in turn plays important role in the treatment of Type 2 diabetes and cardiomyopathy. Keywords: Peroxisome proliferator-activated receptor-Î³ agonists, Thiazolidinediones, Hybrid compounds, Adenosine monophosphate-activated protein kinase activation, Type 2 diabetes, Cardiomyopathy.